1988
DOI: 10.1007/bf00051233
|View full text |Cite
|
Sign up to set email alerts
|

Calcium channel antagonists part IV: Side effects and contraindications drug interactions and combinations

Abstract: With the correct selection of drug and patient, the calcium antagonists as a group can be remarkably effective at relatively low cost of serious side effects. Almost all side effects are dose related. Minor side effects include those caused by vasodilation (flushing and headaches), constipation (verapamil), and ankle edema. Serious side effects are rare and result from improper use of these agents, as when intravenous verapamil (or diltiazem) is given to patients with sinus or atrioventricular nodal depression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(16 citation statements)
references
References 83 publications
0
16
0
Order By: Relevance
“…Leg and ankle swelling is a frequent occurrence while taking calcium channel blockers (CCBs), not only dihydropyridines (DHP) 1 but also verapamil 2 and diltiazem. 3 This troublesome side effect presents as leg and ankle swelling in the absence of sodium retention 4 or cardiac failure 1 and may reach the stage of pitting oedema, thereby requiring discontinuation of an otherwise highly effective antihypertensive therapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leg and ankle swelling is a frequent occurrence while taking calcium channel blockers (CCBs), not only dihydropyridines (DHP) 1 but also verapamil 2 and diltiazem. 3 This troublesome side effect presents as leg and ankle swelling in the absence of sodium retention 4 or cardiac failure 1 and may reach the stage of pitting oedema, thereby requiring discontinuation of an otherwise highly effective antihypertensive therapy.…”
Section: Introductionmentioning
confidence: 99%
“…3 This troublesome side effect presents as leg and ankle swelling in the absence of sodium retention 4 or cardiac failure 1 and may reach the stage of pitting oedema, thereby requiring discontinuation of an otherwise highly effective antihypertensive therapy. This review will focus on the antagonism exerted by CCBs on cutaneous postural vasoconstriction, and the possible contribution of this pharmacological interference to the development of dependent oedema during treatment with CCBs.…”
Section: Introductionmentioning
confidence: 99%
“…7 This pharmacological effect may contribute to ankle and/or pretibial edema in the absence of fluid retention, 8 a frequent, bothersome, and still not completely understood collateral effect of calcium antagonist drugs. 9 To test this hypothesis, we evaluated the relation between changes in postural skin vasomotion and objective measures of ankle swelling during treatment with graded doses of amlodipine, a dihydropyridine CCB. 10 On the basis of previous reports of reduced ankle swelling during association therapy with angiotensin-converting enzyme inhibitors (ACEIs), 11,12 we evaluated those parameters also during amlodipine treatment combined with enalapril, an ACEI.…”
mentioning
confidence: 99%
“…19 The present study demonstrated that, significantly higher total AEs in general, and ankle edema in particular in the long-term management of mild to moderate hypertension. 8 It is generally accepted that in response to blood pressure lowering after amlodipine, the baroreflex-induced activation of the sympathetic system leads to contraction of postcapillary venules, which in turn increases the pressure gradient at the capillary level. Hydrostatic pressure aggravates the phenomenon of capillary transudation.…”
Section: Discussionmentioning
confidence: 99%
“…Dihydropyridine calcium-channel blockers (CCBs) are one of the commonly used potent antihypertensive drugs and their vasodilatory effects are associated with adverse drug reactions (ADRs) such as ankle edema, headache and flushing. 8 Ankle oedema is a dose related common adverse event observed during treatment with CCBs. In many cases, ankle oedema is responsible for treatment discontinuation or limited patient's compliance to anti-hypertensive treatment and has a deleterious impact on healthrelated quality of life.…”
Section: Introductionmentioning
confidence: 99%